2019
DOI: 10.1136/jnnp-2019-321897
|View full text |Cite
|
Sign up to set email alerts
|

Pure tone audiometry and cerebral pathology in healthy older adults

Abstract: BackgroundHearing impairment may be a modifiable risk factor for dementia. However, it is unclear how hearing associates with pathologies relevant to dementia in preclinical populations.MethodsData from 368 cognitively healthy individuals born during 1 week in 1946 (age range 69.2–71.9 years), who underwent structural MRI, 18F-florbetapir positron emission tomography, pure tone audiometry and cognitive testing as part of a neuroscience substudy the MRC National Survey of Health and Development were analysed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 14 publications
0
29
1
Order By: Relevance
“…Another recent article did not find an association between HL and neuropathologic findings of AD on brain autopsies; however, the lack of an objective hearing measure may have limited sensitivity 17 . A study similar to ours that used a different radioisotope ( 18 F‐florbetapir) in an older population did not find an association been audiometric HL and β‐amyloid on PET 16 . The reason for the differing findings from our study are unclear.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Another recent article did not find an association between HL and neuropathologic findings of AD on brain autopsies; however, the lack of an objective hearing measure may have limited sensitivity 17 . A study similar to ours that used a different radioisotope ( 18 F‐florbetapir) in an older population did not find an association been audiometric HL and β‐amyloid on PET 16 . The reason for the differing findings from our study are unclear.…”
Section: Discussioncontrasting
confidence: 87%
“…Data linking HL to more specific brain biomarkers of dementia are largely lacking. The few studies that have been published are mostly null 16–18 . To our knowledge, no study has shown an association between HL and brain β‐amyloid, the characteristic pathologic feature of AD.…”
Section: Introductionmentioning
confidence: 97%
“…This may lead to an unnecessary over‐onward referral for cognitive assessment. A recent cross sectional study found an association between pure tone audiometry and mini‐mental state examination score, possibly accounted for by an MMSE test item that assesses repetition of an auditorally presented sentence 10 . Therefore, the interpretation of cognitive screening test results among hearing loss older adults should be done carefully.…”
Section: Introductionmentioning
confidence: 99%
“…adults with HL (n = 142;[29][30][31][32]), objective audio-280 metric assessment of HL, objective non-screening 281 cognitive assessment data obtained through visual, 282 not auditory, presentation, and the use of the Centiloid scale to allow comparison across different tracers and sites.The data from this study and three of four others examining the relation between HL and A␤ suggest that indices of A␤ are not increased in older adults with HL. Three initial studies (two imaging, one via autopsy) investigated whether there was an association between HL and A␤, with all reporting no association[30][31][32]. However, all three studies were subject to significant methodological limitations.…”
mentioning
confidence: 99%